PENINGKATAN HASIL BELAJAR BIOLOGI SISWA DENGAN MENGGUNAKAN PENDEKATAN MODEL PEMBELAJARAN BASED LEARNING KELAS X DI SMAN 1 TEBING SYAHBANDAR TP 2021 / 2022 - MARNI MANURUNG (JURNAL ILMIAH SIMANTEK, 2022)
Problem Based Learning model is a learning model with a student learning approach to authentic problems so that students can construct their own knowledge, develop higher skills and inquiry, make students independent and increase selfconfidence. This study investigates the usefulness of the model-based learning approach. X grade students of SMAN 1 Tebing Syahbandar as the object of this research. Problem based learning (PBL) is a learning model that involves the activeness of students to always think critically and always be skilled in solving a problem. The workflow of students depends on how complex the problem is. Just like project based learning, the success rate of this method depends on the activeness of the students. The more active students use their thinking skills, the greater the chance of problems to be solved. The purpose of this research is to improve students' critical thinking skills. Train students in solving a problem systematically. Helping students understand the role of adults in real life. Encouraging students to become independent and responsible individuals. This research method uses qualitative methods to collect data from research.